Possible Lingering Effects of Multiple Past Concussions - Iverson, Grant L. (Hindawi Publishing Corporation, 2012)
Background. The literature on lingering or “cumulative” effects of multiple concussions is mixed. The purpose of this study was to examine whether athletes with a history of three or more concussions perform more poorly on neuropsychological testing or report more subjective symptoms during a baseline, preseason evaluation. Hypothesis. Athletes reporting three or more past concussions would perform more poorly on preseason neurocognitive testing. Study Design. Case-control study. Methods. An archival database including 786 male athletes who underwent preseason testing with a computerized battery (ImPACT) was used to select the participants. Twenty-six athletes, between the ages of 17 and 22 with a history of three or more concussions, were identified. Athletes with no history of concussion were matched, in a case-control fashion, on age, education, self-reported ADHD, school, sport, and, when possible, playing position and self-reported academic problems. Results. The two groups were compared on the four neuropsychological composite scores from ImPACT using multivariate analysis of variance followed by univariate ANOVAs. MANOVA revealed no overall significant effect. Exploratory ANOVAs were conducted using Verbal Memory, Visual Memory, Reaction Time, Processing Speed, and Postconcussion Scale composite scores as dependent variables. There was a significant effect for only the Verbal Memory composite. Conclusions. Although inconclusive, the results suggest that some athletes with multiple concussions could have lingering memory deficits.